Key factors affecting health promoting behaviors among adolescents: a scoping review - Jafar Sadegh Tabrizi; Leila Doshmangir; Najibeh Khoshmaram; Elham Shakibazadeh; Hosein Mashhadi Abdolahi; Roghayeh Khabiri (BMC, 2024)
Abstract Background Health-promoting behaviors have been noticed recently as one of the most critical factors in raising life expectancy, which can be formed during adolescence. Thus, the current scoping review aimed to identify the key factors affecting health-promoting behaviors among adolescents. Methods In this scoping review, we searched multiple English online databases, including PubMed, Web of Science, Science Direct, ProQuest, and Scopus, for articles published between 1977 and 2020. All eligible studies describing health-promoting behaviors in adolescents were included. We followed the JBI guideline for conducting a scoping review and increasing the study's rigor. Extracted data were synthesized through inductive approaches. Results A total of 3199 articles were identified during the first phase. After the screening process, 20 articles were found eligible for final inclusion. Educational factors (individualized education and school health promotion programs), Economic factors (income, economic incentives and national health insurance), Social factors (support system, responsibility and peers), Spiritual, Psychological and Personal factors (gender, family structure, patterns of living, and medical problems) were found effective in health-promoting behaviors among adolescents. Conclusions Health-promoting behaviors among adolescents require careful consideration. The current review identified some fundamental factors affecting health-promoting behaviors in adolescents. Based on the findings, it is recommended that policymakers and healthcare providers develop several interventions based on identified factors to increase adolescent's health-promoting behaviors among adolescents.